Formulation of School Rules and Regulations: Balancing Uniformity and Individual Development - Chun, Yangjing (Journal of Educational Research and Policies, 2025)
Balancing uniform norms and personality development is the core relationship to be dealt with in the formulation of school rules and regulations. The formulation of high-quality school rules and regulations should fully recognize that human beings are the unified existence of subjectivity and sociality, and balancing the relationship between uniform norms and individuality development in the formulation of school rules and regulations has the important significance of maintaining the order and safety of the campus, shaping a positive campus culture, promoting the formation of students’ morality and habits, improving the quality and effectiveness of education, safeguarding the lawful rights and interests of teachers and students, promoting the long-term development of schools, and coping with the challenges and changes of the society. It is of great significance that school rules and regulations should be formulated. Therefore, school rules and regulations should be formulated from the aspects of democratic participation, democratic implementation and democratic supervision to balance the relationship between uniform norms and individual development.